Community Initiatives to Preserve and Promote Cultural Heritage - Mumbai, India - Lewis, Ainsley (MAJ - Malaysia Architectural Journal, 2025)
The city of Mumbai is an amalgamation of several communities that migrated and helped build ‘Prime in Indus’. All the architectural built stock has significant cultural and heritage value. Cosmos Indicopleustes in his 6th-century work endorses that the Christian community existed in the Konkan region of India much before the Portuguese. Over the last five decades, the lack of awareness about the importance of the historical and cultural significance resulted in several architectural buildings such as churches, institutes, etc being demolished and artifacts like manuscripts, records, paintings, furniture, and vestments being desecrated, sold or stacked away in storerooms. In 2006 the Archdiocese of Bombay set up a committee of architects, historians, and interested clergy to address this concern. Significant work has been undertaken to preserve and promote the historic and cultural patrimony of the church through its varied programs. The advocacy has borne fruit and led to a transformation in the attitude of 4,91,249 Christians, both religious and laity in the archdiocese. The Archdiocesan Heritage Museum is one of its kind in the metropolis initiated by the committee. It facilitates Catholic community groups who seek guidance to restore churches and artifacts in the vast metropolitan region of 10,100 sq km. The participatory effort to preserve and promote the cultural heritage of the Catholic Community can be used by other communities to prepare a toolkit to establish a place’s cultural significance and conserve the tangible and intangible heritage under severe pressure from urban development.